2013
DOI: 10.13054/mije.13.61.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical Perceptions of Teacher Candidates towards the School Concept: Lotus Flower Model

Abstract: This study aimed to determine teacher candidates's perception about "school" through metaphors. In this respect, components of school such as "Teacher, Student, Principal, Classroom, Teachers' Room, Parent, Ministry of National Education and Inspector" were categorized separately to determine metaphorical images of teacher candidates about school. The sampling of the study consisted of 346 teacher candidates studying at Science, Physics, Chemistry, Biology and Math departments of Hacettepe University, Faculty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
4
0
4
Order By: Relevance
“…The teacher candidates who used metaphors for teacher such as plaster master and carpenter, similarly regarded student as a passive learner with metaphors such as dough, clay, and plaster. Similarly, previous studies (Aydın & Pehlivan, 2010;Koç ak, 2013;Mahlios & Maxson, 1998;Saban, 2009;Saban, 2010) showed that a passive student perception emerged. In addition, a significant number of teacher candidates thought that students are made to overwork (a racehorse), they are uniformized (robot), they are not given the value they deserve (orphan child), and that they are educated unsystematically (subject).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The teacher candidates who used metaphors for teacher such as plaster master and carpenter, similarly regarded student as a passive learner with metaphors such as dough, clay, and plaster. Similarly, previous studies (Aydın & Pehlivan, 2010;Koç ak, 2013;Mahlios & Maxson, 1998;Saban, 2009;Saban, 2010) showed that a passive student perception emerged. In addition, a significant number of teacher candidates thought that students are made to overwork (a racehorse), they are uniformized (robot), they are not given the value they deserve (orphan child), and that they are educated unsystematically (subject).…”
Section: Discussionsupporting
confidence: 70%
“…Some metaphors forming the basis of these perceptions were "jigsaw", "play dough", "test board", "tarhana soup (a traditional Turkish soup)", "Noah's pudding (a traditional Turkish food)", and "labyrinth". The findings of Koç ak (2013) revealed that teacher candidates' perceptions of MoNE (Ministry of National Education) were mostly shaped by metaphors related to politics. These findings involved criticisms of the frequent changes and the complex structure.…”
mentioning
confidence: 99%
“…According to Koçak (2013) metaphors are essential tools for catching the main nature of an experience in an active process, which enables individuals to understand their own worlds along with others. First sub-category is foreign language teachers as caring image represents that teacher candidates perceive foreign language teachers have a caring role in language classrooms.…”
Section: International Journal Of Languages' Education and Teachingmentioning
confidence: 99%
“…Similar results have been obtained in other studies. A study was carried out by Koçak (2013) (1) the manufacturing metaphor; (2) the military metaphor; (3) the gardening metaphor; and (4) the sports metaphor. Another study was carried out in Malasia by Nikitina and Furuoka in 2008.…”
Section: International Journal Of Languages' Education and Teachingmentioning
confidence: 99%
“…The use of metaphor as an investigative tool in the field of education has been highly appreciated. Metaphors can be used as effective tools to determine the role of teachers in modern education (Patton, 2002b;Perry, 1995;Perry & Cooper, 2001;James, 2002;Vadeboncoeur & Torres, 2003), as well as their roles in guiding education and teaching practices (Botha, 2009;Carlson, 2001;Cerit, 2008;Cochran, 2002;Cook-Sather, 2003;Koçak, 2013;Massengill, Mahlios, & Barry, 2005;Zheng & Song, 2010). Moreover, international literature increasingly supports the study and use of teacher's metaphorical images to understand how they conceptualize their teaching and themselves in their field of work (Inbar, 1996;Leavya, McSorley, & Bote, 2007;Martinez, Sauleda, & Huber, 2001;Saban, Koçbeker, & Saban, 2006, 2007Thomas & Beauchamp, 2011).…”
Section: Introductionmentioning
confidence: 99%